BENTUK DAN MAKNA ONOMATOPE DALAM KOMIK ONE PIECE VOLUME 105 KARYA EIICHIRO ODA - Fahmi Suhendra, Arif; Syahrial; Kartika, Diana; Izmayanti , Dewi Kania (Program Studi Sastra Jepang Fakultas Ilmu Budaya Universitas Bung Hatta, 2024)
Onomatopoeia are words that represent sounds or sounds from living creatures, objects, and explain activities or situations that are occurring. Onomatopoeia is often used in literary works such as comics. Comics contain images that appear to speak or move, requiring imitation of sounds and actions to create sound effects and emotions. The aim of this research is to discuss the form and meaning of onomatopoeia in the One Piece comic volume 105 by Eiichiro Oda, which uses Akimoto's theory to analyze the form of full repetition, Oota's theory for the form of repetition of sound changes, and Akutsu's theory for the form of added affixes. Then the type of meaning uses Akimoto's theory. In this research, there are 4 onomatopoeia, namely (1) onomatopoeia giongo (imitation of the sound of inanimate objects), (2) giseigo (imitation of sounds from living things), (3) giyougo (imitation of sounds of states or behavior), and (4) gijougo (imitation of the sound of a mood or feeling). Meanwhile, there are 10 types of meaning, namely, (1) shizengenshou, (2) mono ga dasu oto, (3) doubutsu no nakigoe, (4) hito no koe/oto, (5) mono no ugoki, (6) mono no youtai/seishitsu, (7) hito no dousa, (8) hito no kenkou joutai, (9) hito no yousu/shinjou, and (10) hito no shintaiteki tokuchou. This research method is a descriptive study used to explain the form and meaning of onomatopoeia in the One Piece comic by Eiichiro Oda. In collecting data, the author used the note-taking technique, meanwhile to analyze the data, the author used the technique of selecting determining elements.